(untitled) (Journal of Science and Technology, 2016)
Identification and distribution of fern species on the Kwame Nkrumah University of Science and Technology campus were determined. A dichotomous key was constructed for the identification of ferns on the Kwame Nkrumah University of Science and Technology campus. The species were identified using keys, descriptions, pictures, figures, herbarium specimens and assistance of fern taxonomists. The distribution of the species was determined using the relative frequency. The relative frequency of the species was quantified by recording the presence or absence of the plant species in a set of ten randomly located quadrats (4 m x 4 m). The plot size in each site was 40 m x 40 m. Thirteen different fern species belonging to the following genera were identified: Nephrolepis, Pteris, Microsorum, Cyclosorus, Arthropteris, Thelypteris, Adiantum, and Pityrogramma. The family Pteridaceae was the most diverse in terms of species richness while the family Oleandraceae recorded the lowest number of species. The most widely distributed fern species were Arthropteris orientalis and Thelypteris microbasis. The distribution of the rest of the species was however low. The study also showed that ferns on the Kwame Nkrumah University of Science and Technology campus are distributed in two main habitats: open and shaded. More of the species occurred in the shaded habitats. The diversity and distribution of ferns were affected by human activities.